A framework for the analysis of industrial relations systems - Craig, Alton W.J. (Alton Westwood Joseph); International Industrial Relations Association. World Congress (3rd : 1973 : England). (1973)
The author tried to set forth in skeletal form the main components of a framework for the analysis of industrial relations systems, based largely on a paper he gave to the Canadian Political Science Association in 1967. He also tried to show the framework might be used as a predictive one by way of a few simple examples. And finally, he also tried to show in a very sketchy form, how it might be applied to the analysis of the bipartite, tripartite and the labour market (unorganized) systems that exists in North America.
Introduction -- The main components of the model -- The inputs of an industrial relations system -- Inputs from within the system itself -- Flow of effects from the environment as conditioning inputs into the industrial relations system -- Procedures for Converting the inputs into outputs -- The outputs of industrial relations systems -- The concept of the feedback loop -- The predictive power of the model -- Application of the framework to the co-existing types of "Industrial Relations Systems in North America, i.e. the bipartite, tripartite and enterprise labour market" -- conclusion.
Photocopy.
Paper presented to the International Industrial Relations Association, 3rd, World Congress, 3-7 Sept. 1973.
Includes bibliographical references (leaf 12)
Keywords: Industrial relations